Fifth Industrial Revolution: (New Perspectives) - Ali, Sabah Hameed; Al-Sultan , Hayder Ayad; Al Rubaie, Mithaq Taher (International Journal of Business, Management and Economics, 2022)
While we are rushing towards the future quickly and without stopping, there is a debate in the scientific community and business forums today about the upcoming industrial revolution and what it is related to, is it the revolution of artificial intelligence, or the revolution of nanotechnology, or the revolution of sustainability, or is it the revolution of the Internet of things, cloud computing and 3D printing? We believe that the Fifth Industrial Revolution will be the result of all these technologies. And through our research paper, we will address the concept of the industrial revolution in general and the major industrial revolutions in human history and their historical context. Then we will look at the Fourth Industrial Revolution, whose events we are living today, its most important technologies, and its future development. Then we will look at the future features of the upcoming Fifth Industrial Revolution and the controversy surrounding it from the point of view of several experts and the most important opportunities and challenges that are likely to emerge